Impaired bone and muscle development in young people treated with antiepileptic drugs - Simm, Peter J.; Seah, Sebastian; Gorelik, Alex; Gilbert, Lauren; Nuguid, Jenning; Werther, George A.; Mackay, Mark T.; Freeman, Jeremy L.; Petty, Sandra J.; Wark, John D. (Epilepsia (Copenhagen), 2017)
Summary Objective Antiepileptic drugs (AEDs) are associated with reduced bone density, balance impairment, and increased fracture risk in adults. However, pediatric data are limited. Therefore, we aimed to examine bone, muscle, and balance outcomes in young patients taking AEDs. Methods We undertook a case–control study utilizing an AED exposure–discordant matched‐pair approach. Subjects were aged 5–18 years with at least 12 months of AED exposure. Pairs were twins, nontwin siblings and first cousins, sex‐ and age‐matched (to within 2 years), allowing for greater power than with unrelated control subjects. Dual energy x‐ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT), and muscle force/balance were tested, with questionnaires were administered for bone health and epilepsy details. Results Twenty‐three pairs were recruited, (median age 12.9 years [subjects] and 13.5 years [controls])—7 twin, 14 sibling, and 2 cousin pairs. Those taking AEDs had an increased prevalence of fractures (15 fractures in 8 subjects, compared with 4 fractures in 3 controls, p < 0.01). Trabecular volumetric bone mineral density (vBMD) measured by pQCT at the 4% site (tibia) was reduced by 14% (p = 0.03) in subjects. Subjects exerted a decreased maximum force compared to body weight (Fmax total/g) at the tibia. There were no differences seen in either bone mineral parameters measured by DXA or balance measures. Significance Young people taking AEDs reported more fractures and had reductions in tibial vBMD and lower limb muscle force compared to their matched controls. These findings suggest that further exploration of bone health issues of young patients on AED therapy is required. Longitudinal studies are required to confirm these changes in the muscle–bone unit and to further explore the clinical outcomes.